Novel Herbal Therapeutic YH23537 Improves Clinical Parameters in Ligature-Induced Periodontal Disease Model in Beagle Dogs - Jang-Woo Shin; Eui-Ri Lee; Hyunwoo Noh; Jiyoon Kwak; Ji-Yeong Gal; Hyun-Je Park; Seongkyu Kim; Hyun-Kyung Song; Kangmoon Seo; Beom Seok Han (International Journal of Dentistry)
Currently, available medicine does not satisfy the clinical unmet needs of periodontal disease. Therefore, novel drugs with improved efficacy profiles are needed. We previously demonstrated that YH14642, water extracts of Notoginseng Radix and Rehmanniae Radix Preparata, improved probing depths in double-blind phase II clinical trial. However, it still has hurdles for commercialization due to the low efficiency of active compound extraction. To resolve this issue, we developed YH23537 through process optimization to extract active compounds efficiently while still achieving the chemical profile of YH14642. In this study, we investigated the therapeutic effects of YH23537 compared with YH14642 using a canine model of ligature-induced periodontitis. Human gingival fibroblast (hGF) cells were treated with various concentrations of YH23537 or YH14642 with lipopolysaccharide (LPS) for 24 hr. IL-6 and IL-8 levels in the conditioned media were determined using Luminex. Sixteen 3-year-old male beagle dogs had their teeth scaled and polished using a piezo-type ultrasonic scaler under general anesthesia and brushed once daily for the following 2 weeks. Two weeks after the scaling procedure, the left upper second premolar (PM2), third premolar (PM3), and fourth premolar (PM4) as well as the left lower PM3, PM4, and first molar (M1) were ligated with silk-wire twisted ligatures. The dogs were fed with soft moistened food to induce periodontitis for 8 weeks, and the ligatures were then removed. YH23537 and YH14642 were administered for 4 weeks, and clinical periodontal parameters such as plaque index (PI), gingival index (GI), probing depth (PD), clinical attachment level (CAL), and bleeding on probing (BoP) were determined before and 1, 2, 3, and 4 weeks after treatment. YH23537 inhibited IL-6 and IL-8 secretion in a dose-dependent manner in hGF cells stimulated with LPS. The IC50 values for YH23537 were 43 and 54 μg/ml for IL-6 and IL-8, respectively, while the values for YH14642 were 104 and 117 μg/ml, respectively. In the animal study, clinical parameters including GI, PD, CAL, and BoP were significantly increased after 8 weeks of ligature-induced periodontitis. The YH23537 300 and YH23537 900 mg groups had significant improvements in CAL from 1 to 4 weeks after treatment in comparison to the placebo group. GR values in the YH23537 900 mg group were decreased throughout the treatment period. GI values were also reduced significantly after 4-week treatment with 300 and 900 mg of YH23537. YH23537 at 300 mg doses showed comparable efficacy for CAL and GR with 1,000 mg of YH14642. YH23537 showed therapeutic efficacy against periodontitis in dogs, mediated by anti-inflammatory effects. These findings indicate that YH23537 has the potential for further development as a new drug for patients suffering from periodontal disease.